The Dog that Did Not Bark: Limited Price Efficiency and Strategic Nondisclosure - ZHOU, FRANK S.; ZHOU, YUQING (Journal of Accounting Research, 2020)
ABSTRACT Theory posits that investors can rationally infer the implications of strategic nondisclosure for firm value, pressuring managers to disclose information voluntarily. This study documents that the lack of an earnings guidance predicts an abnormal return of −41 basis points around the subsequent quarterly earnings announcement, suggesting that investors do not fully incorporate the implications of nonguidance. Further analyses demonstrate that limitations in price efficiency, driven by investors' limited attention and short‐selling constraints, explain the mispricing of nonguidance and are associated with less guidance issuance. Our results collectively highlight limited price efficiency as another friction when studying managers' strategic disclosure decisions.